Sustainability reporting and financial performance of Malaysian Public Listed Companies - Kasbun, Nur Fatin; Boon, Heng Teh; Ong, Tze San (Faculty Economics & Administration, University of Malaya, 2016)
Sustainability reporting has become increasingly common in recent years for companies across the globe. It is seen as an approach that can integrate and balance the performance of a business’ economic, environmental and social dimensions. The main issue now is not solely about complying with the mandatory rules or ensuring the company’s reputations, but sustainability to promote efficiency in business and improve productivity. Although sustainability reporting is not a new concept, its implementation is still unsystematic. Management, it appears, is not convinced on the importance of sustainability reporting due to high costs and difficulty of measurements. These have resulted in ignorance, negligence and unsystematic nature of economic, social and environmental reportage on sustainability in Malaysia. Reporting percentage in Malaysia remains very low despite it being ranked the highest in Southeast Asia. Despite the rise in the sustainability reporting globally, there is limited academic research on sustainability reporting in Malaysia while conventional accounting practices somewhat reduced the need for sustainability reporting. This research investigates the relationship between sustainability reporting and financial performance of Malaysian Public Listed Companies. In the summary of findings, the regression results suggest that economic, social and environmental sustainability reporting is positively associated with financial performance measured using Return on Assets and Return on Equity.